2007
DOI: 10.1002/path.2276
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation and inflammation in HIV‐1 infection: causes and consequences

Abstract: Thorough research on HIV is progressively enabling us to understand the intricate mechanisms that link HIV-1 infection to the onset of immunodeficiency. The infection and depletion of CD4 + T cells represent the most fundamental events in HIV-1 infection. However, in recent years, the role played by chronic immune activation and inflammation in HIV pathogenesis has become increasingly apparent: quite paradoxically, immune activation levels are directly associated with HIV-1 disease progression. In addition, HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
544
1
14

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(585 citation statements)
references
References 152 publications
(145 reference statements)
20
544
1
14
Order By: Relevance
“…Moreover, CD4 senescent T cells also express NK cell‐related receptors and high levels of granzyme B and perforin, which may be important for protection against infections in vivo (Appay & Sauce, 2008). Altogether, pro‐inflammatory factors included within the SASP of senescent T cells can cause adverse or positive effects on surrounding nonsenescent cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…Moreover, CD4 senescent T cells also express NK cell‐related receptors and high levels of granzyme B and perforin, which may be important for protection against infections in vivo (Appay & Sauce, 2008). Altogether, pro‐inflammatory factors included within the SASP of senescent T cells can cause adverse or positive effects on surrounding nonsenescent cells.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…Those studies have shown that the proinflammatory cytokines interleukin (IL)-1β, tumour necrosis factor (TNF)-α and interferon (IFN)-γ, and lipopolysaccharide (LPS), are capable of activating the enzyme indoleamine 2, 3-dioxygenase (IDO) [30][31][32], a tryptophan-degrading enzyme that oxidizes tryptophan to n-formylkynurenine. A hallmark of HIV infection is the presence of abnormal levels of immune activation and inflammation with high concentrations of proinflammatory cytokines, and high plasma LPS levels [33]. Therefore, activation of IDO by inflammatory signals was expected in HIV infection.…”
Section: Depression In Hiv-infected Patients 217mentioning
confidence: 99%
“…The analysis of Cozzi-Lepri et al 27 in 2011 also demonstrated a high correlation between VL increase, following treatment interruption, versus a decline of CD4+ T and increases in the production of IL-6, TNF-α and IL-10 by macrophages and/or monocytes. This suggests that the effect of HIV replication in these cells can constitute a critical pathway of HIV induction mediated by immune activation and inflammation, as well as a consequent immunological deficiency 27,64 . Nevertheless, under drug compliance and a good response to therapy, studies have shown that the impact of cART in immune reconstitution is closely related to the reduction of immunological activation due to a decline in VL 65 .…”
Section: Persistent Inflammatory Status After Cart Initiatementioning
confidence: 99%